PENGGUNAAN MEDIA AUDIO UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK SISWA MELALUI CERITA RAKYAT DI KELAS IV SD NEGERI 62 BANDA ACEH - febriani, kurnia; Yamin, M.; Victoria, Linda (Universitas Syiah Kuala, 2023)
The title of this study is The Use of Audio Media to Improve Students' Listening Ability Through Folklore in Grade IV SD Negeri 62 Banda Aceh. This research was conducted as an effort to improve the quality of learning which still tends to use the lecture method from printed books which are delivered orally without using learning media in the learning process, so that in students' listening abilities there are still a few obstacles to the level of student understanding, therefore by using the media this learning can help the problems that occur in students, namely the low ability of students in listening skills. Learning media is a method or tool used in the teaching process. This is done in order to stimulate learning models so that they can support the success of the teaching process, so that the learning activities achieve the desired goals. The learning media used in this study is audio media, namely media that conveys information that will be conveyed in the form of auditory symbols, both verbal (transformed into spoken words or words) and nonverbal (recorder) so that it can have a good impact on students' abilities. listening to students. Folklore is a cultural heritage in the form of stories or stories originating from ancient societies and developed widely from generation to generation until finally it became widely known. There are 3 folklore stories in this study, namely Tuan Tapa Putri Naga, Mentiko Batuah and Atu Belah Atu Bertangkup. This research is in the form of a qualitative approach, the type of research is descriptive. The research was conducted at SD Negeri 62 Banda Aceh, the samples in this study were grade IV students. The data collection technique uses tests and interviews (homeroom teacher), and the data analysis technique used is based on data collection, data presentation, data reduction and drawing conclusions.